The Effect of Fiqh Teacher Creativity on Student Learning Achievement in MTs. Nurul Ulum Mertak Praya Lombok Tengah - Sahdan (Saniya Institute, 2025)
This study investigates the impact of teacher creativity on student achievement in Islamic religious education, with a particular focus on Fiqh (Islamic jurisprudence) instruction at MTs Nurul Ulum Mertak Tombok. A quantitative research design was employed, utilizing data collected through questionnaires and students’ daily test scores. Given that the population exceeded 200, a population-based approach was adopted, involving 243 students from grades VII and VIII. From this population, a stratified sample of 148 students across nine classes was selected. Data collection employed a combination of questionnaires, classroom observations, and documentation, while data analysis was conducted using the Pearson Product Moment correlation technique. The results revealed a statistically significant and positive relationship between teacher creativity and student achievement in Fiqh. Specifically, the correlation coefficient was 0.637, indicating a strong influence of teacher creativity on learning outcomes. These findings highlight the pivotal role of innovative and creative teaching strategies in enhancing the effectiveness of Islamic religious education, particularly in improving student performance in Fiqh.